A Design of Wireless Communication and Wireless Energy Transfer System for In-Pipe Robots - Akafua, Jonathan; Chapman, Ryan; Guo, Hongzhi (IEEE International Conference on Wireless for Space and Extreme Environments conference digest (Online), 2021)
In-pipe robots and underground sensors play an important role in pipeline inspection by providing accurate sensing data. Some of the pipes are made of metal and buried underground. Radio Frequency (RF) signals in such an extreme environment experience significant propagation loss and uncertainty. This paper designs a hybrid wireless energy transfer and wireless communication system for in-pipe robots and underground sensors. The acoustic signals are used for wireless energy transfer. Low Frequency (LF) and High Frequency (HF) magnetic fields are used for through-pipe and near-pipe communications. Full-wave simulations are performed to evaluate the performance. A software-defined communication testbed is designed using QPSK modulation for LF and HF communications. The data rate and wireless channel are measured and analyzed. The results show that at the end of an 8 mm thick metal pipe, the maximum data rate is 50 kbps with a distance of 2 cm and 100 kHz carrier frequency.